Potential of periosteal cells in bone and cartilage regeneration: a systematic review - Cao, Rongkai; Chen, Beibei; Li, Qianru; Qiu, Piaopiao; Liang, Xiaojie; Cao, Yujie (Frontiers in Bioengineering and Biotechnology, 2023)
The unavailability of adequate human primary cells presents multiple challenges in terms of bone and cartilage regeneration and disease modeling experiments in vitro. Periosteal cells (PCs), which represent promising skeletal stem cell sources, could be a promising strategy in tissue engineering.The present study aimed to summarize the characteristics of PCs to investigate the efficacy of these cells in bone and cartilage regeneration in different models, paying special attention to the comparison of bone marrow stromal cells (BMSCs). A comprehensive literature search was conducted in Embase, PubMed/MEDLINE, Web of Science, and Scopus for articles published in English until April 2023. Only original researches in which PCs were employed for bone or cartilage regeneration experiments were included. A total of 9140 references were retrieved. After screening the results, 36 publications were considered to be eligible for inclusion in the present literature review. Overall, PCs demonstrated beneficial bone and cartilage regenerative efficacy compared to the bare scaffold since almost all included studies reported positive results. The 9 studies assessing the differences in bone formation capacity between PCs and BMSCs indicated that PCs exhibited stronger in vivo osteogenic differentiation capabilities compared to BMSCs, while the other study demonstrated stronger chondrogenic potential of BMSCs. PCs demonstrated beneficial to bone regenerative efficacy compared to the bare scaffold with a low risk of most studies included.However, the cartilage formation capacity of BMSCs still needs to be investigated due to the limited research available and the certain risk of bias. PCs exhibited higher osteogenic capabilities compared to BMSCs in combination with various scaffolds in vivo with good evidence. further researches are needed to elucidate the comparative benefits of cartilage regeneration.